From the Politics of Licensing to the Politics of Strategic Natural Resource Exports: State–Business Relati - Jufriansyah, Jufriansyah; Tarupay, Heri Kusuma; Raman, Asrul (IAHN Tampung Penyang Palangka Raya, 2026)
AbstractThis article analyzes a shift in the political-economic arena of strategic natural resource governance in Indonesia, from licensing politics to the politics of strategic natural resource exports. Since the reform era, studies on natural resources have generally placed permits, concessions, decentralization, and local state-business relations at the center of analysis. However, the centralization of strategic natural resource commodity exports shows that control over natural resources no longer stops at licensing and control over production areas. State control is also moving into the post-production stage, particularly through the regulation of production data, price validation, foreign exchange proceeds from natural resource exports (DHE SDA), trade channels, the Export State-Owned Enterprise/DSI, and access to international markets.This research employs a qualitative approach based on document study, using thematic analysis of regulations, institutional documents, statistical data, academic literature, and credible media reports. The findings show that the politics of strategic natural resource exports forms a new arena in the political economy of natural resources. If licensing politics operates at the entry point of production, the politics of strategic natural resource exports operates at the exit point of commodity value. This shift can strengthen the state’s capacity to read data, prices, and value flows in the natural resource sector. At the same time, however, it also creates risks of authority concentration, administrative monopoly, and a stronger need for legal accountability. The contribution of this article lies in broadening the analysis of state-business relations, from the arena of permits and concessions toward the regulation of data, prices, DHE SDA, export channels, and commodity value flows. Keywords: natural resources; licensing politics; the politics of strategic natural resource exports; state-business relations; legal accountability; DHE SDA.